Serum Levels of Interleukins 6, 10, and 13 Before and After Treatment of Classic Hodgkin Lymphoma - Gaiolla, Rafael Dezen [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Niéro-Melo, Ligia [UNESP]; de Oliveira, Delson Elgui [UNESP] (College Amer Pathologists, 2011)
Context.-Interleukins (ILs) 6, 10, and 13 seem to be important in the pathogenesis of Hodgkin lymphoma (HL), but there is insufficient data on the serum levels of these cytokines in patients with HL.Objectives.-To evaluate serum levels of IL-6, IL-10, and IL-13 before and after HL treatment and to determine their potential association with clinical and labQratory parameters.Design.-Serum IL-6, IL-10, and IL-13 levels were quantified in the serum of 27 patients with HL by enzyme-linked immunosorbent assay. Results were evaluated against clinical and laboratory parameters, response to treatment, and presence of infection by the Epstein-Barr virus. As a control group, serum samples from 26 healthy blood donors were evaluated the same way.Results.-Pretreatment serum levels of IL-6 and IL-10 were significantly higher in patients with HL (P < .001), and a significant decrease was observed after treatment (P < .001). Serum IL-13 was undetectable in both patient and control groups. Serum IL-6 was higher in patients with abdominal involvement (P = .02), hepatomegaly (P = .03), B symptoms (P = .02), and anemia (P = .02). Serum IL-10 levels were higher in patients with hypoalbuminemia (P = .04). No association with EBV status was observed. Lymphocytopenia and B symptoms were accurate predictors of IL-6 serum levels before treatment, and higher pretreatment levels of IL-6 were observed in patients with treatment failure (P = .03).Conclusions.-Serum levels of IL-6 and IL-10 were frequently elevated in patients with HL and decreased substantially after conventional chemotherapy. The association of elevated IL-6 and IL-10 levels in serum with some clinical and laboratory features suggests those ILs may be useful biomarkers for monitoring the HL disease and its response to chemotherapy. (Arch Pathol Lab Med. 2011;135:483-489)